Sosialisasi Pengaruh Gadget Terhadap Tumbuh Kembang Anak Tingkat SD dan SLTP Kabupaten Mandailing Natal - Siti Rahma Harahap; Muhammad Tafsir Tambunan (MADANI PUBLISHER INDONESIA, 2025)
The education on gadget usage among elementary and junior high school students was carried out in Mandailing Natal Regency with the organizing committee from the Mandailing Natal Education Office. This event was conducted over two days, with a total of 100 participants from elementary schools and 100 from junior high schools, coming from various schools around the city of Panyabungan. This community service was conducted in the form of a seminar, featuring speakers from higher education academia. Using the service learning method, students were motivated to understand the meaning of the material presented by relating it to their everyday life context, especially regarding gadget use to develop their skills in social, cultural, and family settings. The importance of managing gadget usage was explained by two speakers, and there was also a question-and-answer session. This educational program resulted in the elementary and junior high school students becoming aware of the importance of gadget usage a good gadget. In addition, students instill in themselves the ability to adjust their gadget needs to avoid the negative effects of excessive gadget use. The contribution of this article provides knowledge about the proper use of gadgets among elementary and junior high school students and can serve as a reference for deepening activities related to gadget education.